2001
DOI: 10.1159/000048544
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Chemotherapy with Epirubicin for Treatment of Advanced or Multifocal Hepatocellular Carcinoma

Abstract: Background: The purpose of this retrospective study was to determine the response rate and effect on survival of chemotherapy with epirubicin in non-resectable advanced hepatocellular carcinoma (HCC). Methods: Fifty-two patients with non-resectable disease were treated with epirubicin. A treatment cycle consisted of 20 mg/m2 i.v. on days 1, 8 and 15 and was repeated every 4 weeks to a maximum dose of 1,000 mg/m2. Forty-four patients were eligible for analysis. Results: Out of 44 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…The experience with epirubicin in Hong Kong also suggests its limited activity in HCC, with a response rate of 9% [10]. A retrospective study with single-agent epirubicin, given at a dose of 20 mg/m 2 weekly for three consecutive weeks every 4 weeks, demonstrated a 9% response rate in HCC [11]. Studies in breast cancer have shown that the weekly schedule of epirubicin is a valid alternative and may have a better safety profile [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The experience with epirubicin in Hong Kong also suggests its limited activity in HCC, with a response rate of 9% [10]. A retrospective study with single-agent epirubicin, given at a dose of 20 mg/m 2 weekly for three consecutive weeks every 4 weeks, demonstrated a 9% response rate in HCC [11]. Studies in breast cancer have shown that the weekly schedule of epirubicin is a valid alternative and may have a better safety profile [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Even though locoregional therapies such as hepatic artery ligation Tables I and II (samples were collected or embolization have been developed in the past decades, they have failed to significantly prolong the overall survival of liver cancer patients (22)(23)(24). Despite decades of efforts made by researchers worldwide, the investigation of anti-liver cancer drugs is stagnant (25)(26)(27)(28). Conventionally, the commonly used drugs for liver cancer chemotherapy are 5-fluorouracil, mitomycin C, cisplatin, doxorubicin and their derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Both epirubicin and mitoxantrone have an approximately similar level of antitumor efficacy as doxorubicin (response rates 10 to 25 percent) (Pohl et al,2001;Dunk et al,1985). In contrast, the single agent activity of pegylated liposomal doxorubicin (PLD) is limited (Lind et al, 2007).…”
Section: Antracyclinesmentioning
confidence: 99%